Administrative employees’ workplace motivation at a South African University - A. Reuben Karabo Makgene; B. Sharol Sibongile Mkhomazi (Jurnal Manajemen Indonesia, 2025)
The purpose of the study was to determine the factors that contribute to the administrative employees’ workplace motivation at a South African university. In this study, 123 administrative employees were identified and only 112 administrative employees took part in the study. A quantitative research approach in the form of a closed-ended questionnaire was adopted in order to collect data and conduct a descriptive analysis. The findings of the study indicate a positive correlation between the identified factors that motivate administrative employees in their workplace. Job security, rewards and remuneration and job advancement opportunities were ranked as top three of the most important motivating factors for the administrative employees. Since there are different factors of motivation, it is thus important for management to possess sufficient knowledge and understanding these employee motivating factors in order to effectively improve and maintain efficient organisational performance. The findings of this study can be adopted as a guideline for the formulation of employee motivation strategies in academic institutions.